Targeted mentoring for human immunodeficiency virus programme support in South Africa - Jobson, Geoffrey (South Afr J HIV Med, 2019)
BACKGROUND: Mentoring is a required component of health systems strengthening technical assistance interventions in low- and middle-income countries (LMICs). Mentoring is useful because it does not necessarily compromise service delivery and promotes the sharing of newly acquired knowledge and skills. However, there is a lack of research on the implementation of mentoring in the context of the HIV epidemic in southern Africa. OBJECTIVES: This qualitative evaluation focussed on understanding the implementation process of targeted mentoring for clinical practice, data management and pharmacy management, at public health care facilities in South Africa; and on identifying critical factors influencing the effectiveness of mentoring as a technical assistance intervention in this context. METHODS: Purposive sampling was used to select participants from public health facilities in three South African Provinces. Participants were invited to take part in structured interviews. Datawere analysed using thematic analysis, and two core themes were identified: mentoring as knowledge and skills transfer; and mentoring as psychosocial support. RESULTS: In terms of knowledge and skills transfer, the sequential implementation of proactive and reactive mentoring was critical. Initial proactive mentoring involved mentors initiating training and developing professional relationships with mentees. Thereafter, a reactive mentoring phase allowed mentees to request support when required. This enabled mentors to leverage real-world problems faced by health workers to support their implementation of new knowledge and skills. The availability and accessibility of mentors alongside the relationships between mentors and mentees provided psychosocial support for health care workers which facilitated their self-efficacy in implementing new knowledge and skills. CONCLUSION: These findings suggest that the success of mentoring programmes in LMICs may require specific attention to both knowledge transfer and the management of interpersonal relationships.